Wireless LAN Access Point Placement Based on User Mobility - Taufiq, Muhammad; Abdullah, Mohd Fikri Azli; Choi, Deokjai (Springer US, 2011)
In a wide area campus, a university provides Wireless Local Area Network (WLAN) for users to connect to the Internet. Most users take advantage of this WLAN benefit by using their laptops. However, the number of smart phone users is growing fast. Since a smart phone is able to get an Internet connection using WLAN, users can use their smart phones without having to pay for a cellular operator. Users tend to use their smart phones more, due to their higher mobility compared to a laptop. This capability enables new services in the market, such as Fixed-Mobile Convergence (FMC), which integrates a fixed network (traditional telephony, WLAN) and a mobile network (cellular) to provide seamless voice communications anytime, anywhere. These new applications require a WLAN connection availability nearly everywhere. However, due to limited budgets, a university can only install APs in places with a high connection demand. We propose a novel WLAN AP placement technique that takes user mobility into consideration. This new approach is more complete than previous approaches, which mainly focus on coverage area and throughput data. Our technique has been implemented in our university. The results show the suitability of the WLAN access point locations in our university campus based on user mobility and activities.